Analysis of Borax and Formalin in Wet Noodles From Sidoarjo Traditional Market: Analisis Boraks dan Formalin dalam Mi Basah dari Pasar Tradisional Sidoarjo - Cicik Herlina Yulianti; Surahmaida (Journal Pharmasci (Journal of Pharmacy and Science), 2023)
Wet noodles are a type of noodle with a fairly high water content (35-52%), so it is easy to spoil if stored for more than 12 hours at room temperature. Misuse of the addition of borax and formalin by irresponsible food manufacturers, aims to make wet noodles last longer. This study aims to determine whether the wet noodles sold in several traditional markets in Sidoarjo contain harmful ingredients borax and formaldehyde. The research design in this study began with organoleptic observations on several wet noodles found in several traditional markets in Sidoarjo Regency, followed by a borax test using a borax rapid test kit and a formalin test with UV Vis spectrophotometry and Nash reagent. Based on the test results, it can be concluded that organoleptic observations showed that there were 3 samples of wet noodles with a floury smell and 5 samples with a sour smell, in terms of texture all samples showed a soft and easily broken texture while in terms of color there were 5 samples that were pale yellow and 3 samples were bone white. Based on the results of the qualitative test of borax, all samples of wet noodles were negative for borax and based on the results of the quantitative test of formalin with UV Vis spectrophotometry, showed a negative result of formalin.